Myomatous hepatic angiomyolipoma: imaging findings in 14 cases with radiological–pathological correlation and review of the literature - Zhu, Z (The British Institute of Radiology., 2014)
OBJECTIVE: To display and analyse the imaging features of myomatous hepatic angiomyolipomas (MHAMLs). METHODS: The imaging features (CT = 9; MRI = 10; ultrasound = 10; contrast-enhanced ultrasound = 4) of 14 patients with pathologically proven MHAMLs were reviewed retrospectively. RESULTS: MHAMLs were surgically resected in the 14 patients (10 females and 4 males; age, 27–64 years; mean, 45 years), all of whom had negative hepatitis markers and were positive for the immunohistochemical stain homatropine methylbromide-45. The tumours were solitary and well defined, and ranged in size from 1.9 to 9.1 cm (mean, 5.7 cm). On dynamic contrast-enhanced CT, MRI and ultrasound scans, all tumours showed fast strong enhancement in the arterial phase and moderate washout in the portal venous and delayed phases, and the greater portions of the tumours were slightly lower than the surrounding hepatic parenchyma. In some cases, a small area of prolonged or increasing enhancement in the tumour was recognized in the delayed phase. Early draining vessels to the portal vein or hepatic vein could be seen in some cases. However, no capsular signs could be confidently identified in the delayed phase. Haemorrhagic cavities were recognized in two cases, and nodular low-intensity areas in the tumours on T(2) weighted imaging that showed slow and faint enhancement on dynamic scans were seen in two cases. However, no necrosis was identified. CONCLUSION: Dynamic enhanced imaging studies revealed some specific features of MHAMLs that distinguish them from other hypervascular hepatic tumours, especially when combined with clinical features. Familiarity with imaging and clinical features of MHAMLs could avoid unnecessary surgical resection of these generally benign tumours. ADVANCES IN KNOWLEDGE: This article systematically describes the imaging features of MHAMLs.